KAJIAN TENTANG SISTEM PENGENALAN BUAH PADA PLATFORM IOS MENGGUNAKAN METODE COLOR HISTOGRAM - Bryce Clement Sutedja; Lina Lina; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Today the use of the mobile phone as an information retrieval system has become a frequently performed. Mobile phone that is easy and practical to carry anywhere, lightweight and increasingly advanced technology makes the device more efficient to use a mobile phone than a desktop or laptop. On basis of these, designed an application to recognize fruit using color histogram method for people affected by Alzheimer. This application is made using xcode with objective-c programming language. The application is built in the iOS platform, the operating system used on the mobile device technology company Apple, the iPhone. Keywords : Color Histogram, iOS, Xcode, Objective-c, Fruit,iPhone.